Assessment of Welders Exposure to Carcinogen Metals from Manual Metal Arc Welding in Gas Transmission Pipelines, Iran - F Golbabaei; M Seyedsomea; A Ghahri; H Shirkhanloo; M Khadem; H Hassani; N Sadeghi; B Dinari (Tehran University of Medical Sciences, 2012)
Background: Welding can produce dangerous fumes containing various metals especially carcinogenic ones. Occupational exposure to welding fumes is associated with lung cancer. Therefore, welders in Gas Transmission Pipelines are known as a high-risk group. This study was designed to determinate the amounts of metals Cr, Ni, and Cd in breathing zone and urine of welders and to assess the possibility of introducing urinary metals as a biomarker due to occupational exposure.Methods: In this cross sectional study, 94 individuals from Gas Transmission Pipelines welders, Iran, Borujen in 2011 were selected and classified into 3 groups including Welders, Back Welders and Assistances. The sampling procedures were performed according to NIOSH 7300 for total chromium, nickel, and cadmium and NIOSH 7600 for Cr+6. For all participants urine samples were collected during the entire work shift and metals in urine were determined according to NIOSH 8310.Results: Back Welders and Assistances groups had maximum and minimum exposure to total fume and its elements, respectively. In addition, results showed that there are significant differences (P<0.05) between Welders and Back Welders with Assistances group in exposure with total fume and elements except Ni. Urinary concentrations of three metals including Cr, Cd and Ni among all welders were about 4.5, 12 and 14-fold greater than those detected in controls, respectively. Weak correlations were found between airborne and urinary metals concentrations (R2: Cr=0.45, Cd=0.298, Ni=0.362). Conclusion: Urinary metals concentrations could not be considerate as a biomarker for welders' exposure assessment.